Rare cause of extrapulmonary tuberculosis in an immunocompetent elderly patient - Srishti Tiwari; Gaurav Sharma; Anup Singh (Journal of Family Medicine and Primary Care)
Tubercular hepatic abscesses in the geriatric population are rare and often misdiagnosed, frequently leading to delayed or presumptive treatment based on tissue biopsy findings. Early and accurate diagnosis using advanced diagnostic tools is crucial for improving prognosis. We present the case of a 65-year-old immunocompetent male who reported a three-month history of fever and one month of right hypochondrial pain. Diagnosis of a tubercular hepatic abscess was confirmed using a cartridge-based nucleic acid amplification test (CBNAAT), which isolated Mycobacterium tuberculosis sensitive to rifampicin. The patient was treated successfully with a standard anti-tubercular regimen. Although cases of tubercular liver abscesses have been documented, using CBNAAT for direct identification from pus samples is rare. Misidentification of such abscesses as bacterial or neoplastic often results in inappropriate treatment, increasing the risk of mortality. This case highlights the importance of early diagnosis and prompt initiation of appropriate therapy to improve outcomes.